OPTIMIZATION OF MIXING TEMPERATURE AND SONICATION DURATION IN LIPOSOME PREPARATION - Dina Christin Ayuning Putri; Rini Dwiastuti; Marchaban Marchaban; Akhmad Kharis Nugroho (Sanata Dharma University, 2017)
Liposomes are a delivery system used in pharmaceutical products and cosmetics. Liposomes have many advantages such as increase stability and efficacy, can be targeted to reduce toxicity and increase accumulation at the target site and are biocompatible. Preparation of liposomes can be done by conventional or new methods which are still being developed. Conventional methods often require a long time and organic solvents which may be toxic. Heating (Mozafari method) is one of the new methods developed in the manufacture of liposomes without organic solvents. Mixing temperature can affect the physical properties of liposomes. The particle size has become one of the important physical properties because it affects the absorption of the drug. Sonication is an easy method of choice in reducing the size of liposomes. Optimization of mixing temperature and duration of sonication in liposomes preparation using new heating methods and sonication were performed by factorial design with 2 factors and 3-levels to obtain optimal liposome size. Data were analyzed with two-way ANOVA. The results showed that both mixing temperature and sonication duration significantly affect liposome size, but the interaction was not statistically significant. Data analysis also showed that mixing temperature, sonication, and their interaction do not affect the polydispersity index of liposome. Results showed the optimum mixing temperature and sonication duration that can produce liposomes with size below 100 nm is at 60C for 30 minutes.